2014
DOI: 10.1111/exd.12402
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AID in malignant melanoma with BRAFV600E mutation

Abstract: BRAF-activating somatic mutations often exist in malignant melanoma. The underlying molecular mechanism of somatic BRAF mutation inductions remained to be clear. Activation-induced cytidine deaminase (AID), a member of a cytidine deaminase family, and APOBEC3B induce somatic mutations and recently have been indicated to be involved in the pathomechanism of several kinds of cancers. The aim of this study was to explore the expression level of AID and APOBEC3B in BRAF-mutation-containing malignant melanoma. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…As mentioned, both are components of ovulation. AID has been implicated in inflammation-associated malignancies [28], [29], such as Helicobacter pylori –induced gastric adenocarcinoma [30], [31], HBV-related hepatocellular carcinoma [32], [33] and cholangiocarcinoma [34], and also in breast carcinoma [35], and malignant melanoma [36]. AID is up-regulated as early as in esophageal intraepithelial squamous carcinoma, and persists in invasive carcinoma [37].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, both are components of ovulation. AID has been implicated in inflammation-associated malignancies [28], [29], such as Helicobacter pylori –induced gastric adenocarcinoma [30], [31], HBV-related hepatocellular carcinoma [32], [33] and cholangiocarcinoma [34], and also in breast carcinoma [35], and malignant melanoma [36]. AID is up-regulated as early as in esophageal intraepithelial squamous carcinoma, and persists in invasive carcinoma [37].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the induction of a point mutation is speculated to be closely associated with carcinogenesis. When the expression of AID was examined in malignant melanoma, it was revealed that malignant melanoma with high expression of AID frequently causes BRAF V600E mutation and has a poor prognosis [17] .…”
Section: Aid and Malignant Melanomamentioning
confidence: 99%
“…The majority of melanoma mutations are C>T transitions, and while primarily due to UV light, other processes may play a role. Okura et al ., demonstrate immunohistological evidence of deaminating enzymes, activation‐induced cytidine deaminase (AID) and apolipoprotein B mRNA‐editing enzyme catalytic polypeptide‐like 3B (APOBEC3B) in melanoma with AID expression enriched in BRAF mutant tumors . APOBEC3B is thought to play a role in innate immunity against endogenous retroelements and exogenous viruses .…”
Section: Commentarymentioning
confidence: 99%